Online Teaching Administration and Academic Staff Effectiveness in Public Universities: An Empirical Study of Budgeting, Coordination, and Supervision in South-west Nigeria - Rasheedat Oladunni Ajape; Olaolu Paul Akinnubi; Yusuf Suleiman (Eduvis : Jurnal Manajemen Pendidikan Islam, 2025)
The integration of technology in education, particularly accelerated by the COVID-19 pandemic, has compelled public universities in South-west Nigeria to shift towards online teaching. This study investigates the critical administrative factors—budgeting, coordination, and supervision—influencing academic staff effectiveness in this new educational landscape. Utilising a quantitative research design, data were collected from 610 academic staff members across various universities through structured questionnaires. Statistical analyses, including correlation and hypothesis testing, were conducted to examine the relationships between the identified constructs and academic staff effectiveness. The findings reveal a significant positive relationship between adequate budgeting, effective coordination, and supportive supervision with academic staff effectiveness. Specifically, the study found that universities with robust budgeting strategies and coordinated efforts among faculty and administration reported higher staff morale and improved teaching quality. Additionally, the lack of regular supervisory feedback was highlighted as a barrier to professional growth for many academic staff. In conclusion, addressing the challenges associated with budgeting, coordination, and supervision is essential for enhancing the effectiveness of academic staff in online teaching. This research contributes to the existing literature by providing actionable insights for university administrators and policymakers, emphasising the need for comprehensive administrative frameworks. By focusing on these critical areas, public universities can better equip their faculty to meet the evolving demands of education in the digital age, ultimately leading to improved student educational outcomes.